Comparison of the DFT-SAPT and Canonical EDA Schemes for the Energy Decomposition of Various Types of Noncovalent Interactions - Stasyuk, Olga A; Sedlak, Robert; Guerra, Célia Fonseca; Hobza, Pavel (Journal of chemical theory and computation, 2018)
Interaction energies computed with density functional theory can be divided into physically meaningful components by symmetry-adapted perturbation theory (DFT-SAPT) or the canonical energy decomposition analysis (EDA). In this work, the decomposition results obtained by these schemes were compared for more than 200 hydrogen-, halogen-, and pnicogen-bonded, dispersion-bound, and mixed complexes to investigate their similarity in the evaluation of the nature of noncovalent interactions. BLYP functional with D3(BJ) correction was used for the EDA scheme, whereas asymptotically corrected PBE0 functional for DFT-SAPT provided some of the best combinations for description of noncovalent interactions. Both schemes provide similar results concerning total interaction energies and insight into the individual energy components. For most complexes, the dominant energetic term was identified equally by both decomposition schemes. Because the canonical EDA is computationally less demanding than the DFT-SAPT, the former can be especially used in cases where the systems investigated are very large.